Hybrid open/closed resection procedure for ancient retroperitoneal Schwannoma: case report and review of the literature. Issue 5 (2nd September 2016) - Baten, Evert; Lerut, Jan; Kempeneers, Ivo
Abstract: Background: Retroperitoneal, ancient Schwannomas are rare tumors that arise from neural sheath Schwann cells. Due to their location and size, these benign tumors can become symptomatic and need surgery. Laparoscopic resection is rarely performed for retroperitoneal Schwannomas. Based on a case report and review of the literature the advantages of a laparoscopic approach are discussed. Methods: A case of laparoscopic resection of a retroperitoneal Schwannoma is reported. An extensive literature search was done in relation to this pathology, 16 papers were included for in depth analysis. Results: Laparoscopic surgery facilitates the dissection of the tumor from surrounding tissues due to a magnified view and optimal visualization of the tumor. Shorter hospital stay, faster recovery, better cosmetic result, less blood-loss and post-operative pain are all advantages of a laparoscopic resection. Disadvantages are a steep learning curve, higher cost and prolonged operation duration. Conclusions: Laparoscopic resection of, even large, retroperitoneal Schwannomas is feasible. In case of vertebral invaded tumors a hybrid approach is recommended.